BELOW BOILING POINT: NEGOTIATING CONFLICT THRESHOLDS IN DISTRIBUTED WORK - Filipova, Anna; Cho, Hichang (AoIR Selected Papers of Internet Research, 2014)
Virtual teams are no longer well-defined organizations with fixed start and end points, but increasingly, entities with fluid boundaries. Consequently, we need to evolve our understanding of their internal processes. Conflict is one such process that has traditionally been split into discrete categories for examination of individual effects on group outcomes. Instead, the present study examines conflict as a whole by focusing on thresholds of conflict emergence in the unique techno-social context of Free and Open Source Software (FOSS) development. Following interviews with diverse representatives of FOSS teams, a grounded theory approach reveals that conflict develops as a combination of, rather than result of any one technological or social factor. In addition, conflict may change states and evolve over time. Finally, different teams with varying structures may take different approaches to conflict with equally successful outcomes. Findings suggest a re-evaluation of what we know about virtual group processes.